CONSIDERING WILLIAM JAMES' CONCEPT OF RELIGION FOR TOLERANCE RELIGIOUS GOVERNANCE MODEL IN INDONESIA - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2026)
According to its constitution (Article 29, Paragraphs 1 and 2), Indonesia guarantees every citizen the right to practice a religion and worship according to their respective beliefs. However, there are organized religions, tribal or local religions, and belief systems (aliran kepercayaan) whose religious rights are not guaranteed, experiencing restrictions and even repression in practicing their faith. One cause of this anomaly is the definition of religion used as the basis for policy in Indonesia. Religion is still narrowly defined, characterized by an Abrahamic religion lens, as a